Inhancing Educational Quality through Madrasah Principal Managerial Competence - Sukarman; Muyasaroh, Siti; Khoiruddin, Muhammad; Mahalli; Kalupae, Abdulasi (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Excellent education requires good management. However, in reality, Madrasahs remain weak in planning, human resource management, curriculum and learning management, facilities and infrastructure management, financial management, public relations management, quality management, student management, and leadership management. The Madrasah principal is one of the most important components of education that plays a crucial role in improving educational quality. Each Madrasah principal has full responsibility for all operational aspects of the Madrasah's operations, from planning, organizing, directing, coordinating, and supervising to ensuring quality education. This study aims to describe the role of the Madrasah principal's managerial competence in improving educational quality at MTs Miftahussalam 1 Wonosalam Demak, MTs Jogoloyo Demak, MA NU Salafiyah Demak, MA Miftahul Huda Jepara, MA Darul Hikmah Jepara, MA Wahid Hasyim Jepara, MA Manahijul Huda Pati, MA Madarijul Huda Pati, MA Sirojul Anam Pati. The research questions are formulated as follows: 1) What is the role of the Madrasah principal's managerial competence in improving educational quality at Madrasah. 2) What are the direct and indirect supporting and inhibiting factors in improving educational quality at Madrasah? 3) How does the principal's managerial competence affect the quality of education at the Madrasah? This research is a case study with a descriptive approach. Data collection used interviews, observation, and documentation techniques. Data were analyzed using data reduction and data presentation, and finally, conclusions were drawn. The results indicate that 1) the principal's managerial role is quite good, having established several educational standards to improve the quality of education through planning, implementation, development, and evaluation in the areas of curriculum, facility and infrastructure management, strengthening community relations, student activity management, and madrasah financing management. 2) Direct supporting factors consist of qualified madrasah human resources and adequate facilities and infrastructure. Indirect supporting factors include the active role of parents and foundation support. Meanwhile, direct inhibiting factors include a limited budget and low student motivation. Indirect inhibiting factors include the shared location with the Madrasah Aliyah and the students' social environment, which contributes to a less conducive learning environment. 3) The quality of education at MTs Miftahussalam is good based on academic and non-academic achievements, appropriate teacher qualifications, good learning quality, use of information technology, and student engagement.